2017
DOI: 10.1093/mnrasl/slx026
|View full text |Cite
|
Sign up to set email alerts
|

Concordance cosmology without dark energy

Abstract: According to the separate universe conjecture, spherically symmetric sub-regions in an isotropic universe behave like mini-universes with their own cosmological parameters. This is an excellent approximation in both Newtonian and general relativistic theories. We estimate local expansion rates for a large number of such regions, and use a scale parameter calculated from the volume-averaged increments of local scale parameters at each time step in an otherwise standard cosmological N -body simulation. The parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 28 publications
3
60
0
1
Order By: Relevance
“…3 After submission of the present paper, we found that Rácz et al (2016) derived an almost identical ΛCDM-proxy value.…”
Section: λCdm As An Observational Proxymentioning
confidence: 62%
See 1 more Smart Citation
“…3 After submission of the present paper, we found that Rácz et al (2016) derived an almost identical ΛCDM-proxy value.…”
Section: λCdm As An Observational Proxymentioning
confidence: 62%
“…Here, we argue that the Hubble constant H bg 1 needed to normalise this background EdS model at early epochs, such that the present effective scale factor is unity, cannot be chosen arbitrarily, since it is observationally constrained. The value of H bg 1 will be needed, in particular, for N-body simulations that are modified to be consistent with the general-relativistic constraints imposed by scalar averaging (Roukema et al, in preparation) and for other simulational approaches working towards general-relativistic cosmology (Giblin et al 2016a,b;Bentivegna & Bruni 2016;Adamek et al 2016;Rácz et al 2016;Daverio et al 2016;Macpherson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Various alternatives to the cosmological constant have been proposed including modified gravity (Clifton et al 2012), scale-invariant (Maeder 2017) or spatially inhomogeneous cosmological models (see e.g. Dunsby et al 2010;Rácz et al 2017). As a consequence of the accelerated expansion of the universe, cosmic microwave background (CMB) photons passing through gravitational potential wells, caused by large scale structure such as galaxy clusters, are left with a net gain of energy as the potential wells become shal-E-mail: behzad.ansarinejad@durham.ac.uk lower as the photons cross them.…”
Section: Introductionmentioning
confidence: 99%
“…Known for twenty years, the result of is key to Newtonian cosmology, and is uncontroversial among researchers working on backreaction problems. However, Kaiser's re-statement that Newtonian models cannot lead to non-vanishing backreaction is correct globally, and relevant for the rebuttal of recent work by Rácz et al (2017) on backreaction calculated within the Newtonian framework. We therefore discuss this latter work, as well as a recent complementary work by Roukema (2017), and we point out why the conclusions drawn from these models on the possibility of global backreaction contradicts the result of .…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%